Agrarian Conflict Dynamics: PT. Nafasindo through Dahrendorf’s Lens - Rani Putri (Program Magister Administrasi Publik, 2024)
Agrarian conflict represents a form of social tension that reflects inequality in the control, utilization, and distribution of natural resources, particularly land. This study focuses on the conflict between the people of Aceh Singkil Regency and PT. Nafasindo, analyzed through the lens of Ralf Dahrendorf’s social conflict theory. The research employs a qualitative approach using the library research method. Data were obtained from secondary sources such as official documents, reports from land agencies, academic publications, and relevant media coverage. The analysis was conducted through the stages of data reduction, data presentation, and interpretive conclusion drawing to understand the social, legal, and political contexts surrounding the conflict.The findings indicate that the conflict began in 2006 and escalated in 2025 following the expiration of PT. Nafasindo’s Land Use Rights (HGU) covering an area of 3,007 hectares. The imbalance of authority between the company as the dominant group and the community as the subordinate group constitutes the main source of conflict. Within Dahrendorf’s theoretical framework, this conflict reflects the community’s effort to renegotiate power relations and demand agrarian justice. The study recommends resolving the conflict through participatory mediation and the reformulation of agrarian policies that uphold the social function of land.